2003
DOI: 10.1108/02634500310480086
|View full text |Cite
|
Sign up to set email alerts
|

Regulating ageism in UK advertising: an industry perspective

Abstract: Demographic trends are suggesting that older people are growing in importance in the population. The advertising industry has been accused of ignoring older people in advertisements, or treating them inappropriately. In order to respond to accusations of ageism within the industry it is suggested that regulation may be required to raise the awareness of advertisers and agencies to the importance of older people, and to encourage more age diverse advertising. This paper presents the findings of a study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…It would not be surprising if such statistics alone provided sufficient motivation for companies to recognize over-65s as a crucially important marketing segment (Gunter, 1998; Tréguer, 2002). However, advertising has been criticized for neglecting older consumers, as well as for being an agent for the perpetuation of ageism (Carrigan & Szmigin, 1999, 2003), arguments that will be discussed in more detail in the “Literature review” section. First, however, it is necessary to provide a brief explanation of why television advertising, in particular, has been chosen as the focus of the present research.…”
Section: Introductionmentioning
confidence: 99%
“…It would not be surprising if such statistics alone provided sufficient motivation for companies to recognize over-65s as a crucially important marketing segment (Gunter, 1998; Tréguer, 2002). However, advertising has been criticized for neglecting older consumers, as well as for being an agent for the perpetuation of ageism (Carrigan & Szmigin, 1999, 2003), arguments that will be discussed in more detail in the “Literature review” section. First, however, it is necessary to provide a brief explanation of why television advertising, in particular, has been chosen as the focus of the present research.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that older people are very often represented stereotypically and negatively (see Carrigan & Szmigin, 2003;Meisner, 2020;Soto-Perez-de-Celis, 2020), indicating that the limited media representations give dominant meanings to older people in society.…”
Section: Stereotypical Representations Of Older Peoplementioning
confidence: 99%
“…This also resonates with educational interventions proposed by other researchers. For instance, Carrigan and Szmigin (2003) argued for explicit policy and educational interventions to help the British advertising industry to steer clear of offensive representations of older people. Milner et al (2012) suggested establishing a post-secondary institution that can provide professional training for media professionals on the heterogeneity of the older population and increase the market's knowledge about healthy and active ageing.…”
Section: Mitigating Ageism In Social Mediamentioning
confidence: 99%
“…Employers with a high share of older workers (50+ years) in their respective companies are more likely to report that older workers are less often sick than their younger counterparts, whereas management personnel from 'younger' companies do not share this perception (Stettes 2009). Whereas sectors such as agriculture and fishing are known for employing the oldest workforces (Macinol 2010), in sectors with a predominantly younger workforce such as advertising (Carrigan and Szmigin 2003), older job seekers are often more liable to age discrimination (Richardson et al 2013). Nevertheless, this behaviour is reported to go both ways.…”
Section: Industrial and Sectorial Affiliationmentioning
confidence: 99%